The effects of political reservations for women on local governance and rural service provision - Raabe, Katharina; Sekher, Madhushree; Birner, Regina (International Food Policy Research Institute, 2009)
In 1993, India introduced quota-based political reservations for women in rural areas with the objective to promote gender equality in human development by making rural service provision and local governance inclusive and responsive to the needs of women. Recent evidence shows that reservation policies for women (1) stimulate the political participation of women in rural areas, (2) shift rural service provision to public goods that reflect gender preferences, and (3) improve the access to and the quality of public services. Despite the suggested positive effects of women’s reservation policies on service provision and local governance, the gender bias in human development is still pronounced. This casts doubt on the effectiveness of reservation policies as an instrument for making rural service provision and local governance more gender equitable and raises questions about the nature and direction of the major constraints. This paper aims to qualify and quantify the role of political reservation policies for women as a determinant of rural service provision and local governance and seeks to identify the social, economic, and institutional factors that constrain effective local governance and rural service provision beyond the women’s reservation effect. Our empirical sample consists of 80 Gram Panchayats (GP) and 966 households in 12 districts in Karnataka in 2006. In contrast to the main existing literature, the empirical evidence from (non-)linear probability models lends weak support to the existence of gender effects of reservation policies on local governance and rural service provision. The local governance and service delivery outcomes are predominantly determined by social, economic, and institutional factors that are unrelated to women’s reservation requirements. For example, (1) individual characteristics such as literacy, household institutional and political linkages, or the household location in the GP and (2) GP-specific factors such as the degree of community involvement in service provision and the fiscal devolution of activities are more likely to have a significant effect on service provision and governance than reservation policies for women. These results suggest that women’s reservation policies per se are insufficient means for making rural service provision and local governance more inclusive and gender equitable. In addition, it appears that gender-integrated policy approaches that are targeted at both women and men are needed.